Death of a Prairie Boy - Dercksen, Judy (Ars Medica, 2025)
As a family physician with lived experience of complex post-traumatic stress disorder, C-PTSD, I seemed to attract a patient panel rich with similarly neurodiverse personalities. Marginalized members of communities require more time and also trauma-informed care, but it is only after I tended to my own mental health that I was truly able to appreciate the need for latitude when it comes to managing the healthcare of those who have experienced a lifetime of health inequity. "Death of a Prairie Boy" reflects how past and current trauma affects judgement and the ability to manage chronic illness.